Exporting Russian Higher Education in the Conditions of a New Reality - V. K. Nikolaev (Moscow Polytechnic University, 2022)
The article addresses the mechanism to raise the competitiveness and attractiveness of the Russian higher education in the international educational market through the development of educational services exporting. Currently, the Russian universities have made progress in international students engagement. According to date for 2021, there are 310 thousand of international students studying at Russian universities, which is approximately 8% of the total amount of students. These figures have been achieved due to the large national strategic projects implementation in the sphere of higher education internationalization. In 2021, the Government of the Russian Federation set a new goal to increase the number of international students motivated to study at Russian universities by 50 per cent. In the conditions of the COVID-19 pandemic, achieving the target figures is possible with the use of the modern tools for the university brand promotion in the world educational space.